2003
DOI: 10.1002/ijc.11498
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nitric oxide on cyclooxygenase‐2 (COX‐2) overexpression in head and neck cancer cell lines

Abstract: The overexpression of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) has been previously reported in head and neck squamous cell carcinoma (HNSCC), as well as in many cancers. We hypothesized that endogenous nitric oxide (NO) might increase the expression of COX-2 in cancer cells. Therefore, we investigated the cross-talk between NO and the prostaglandin (PG) pathways in HNSCC cell lines. We found that COX-2 and iNOS expressions were elevated simultaneously. On adding the NO donor, SNAP, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 42 publications
5
44
0
Order By: Relevance
“…Recently, we showed that NO induces COX-2 expression and prostaglandin E 2 (PGE 2 ) production in head and neck cancer cells, and that this effect is blocked by iNOS inhibitors. Similar results have been shown in other cancer cells, including hepatocarcinoma, gastric cancer and cervical cancer (Park et al, 2003).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Recently, we showed that NO induces COX-2 expression and prostaglandin E 2 (PGE 2 ) production in head and neck cancer cells, and that this effect is blocked by iNOS inhibitors. Similar results have been shown in other cancer cells, including hepatocarcinoma, gastric cancer and cervical cancer (Park et al, 2003).…”
Section: Introductionsupporting
confidence: 89%
“…We previously reported that NO induces COX-2 expression in cancer cells (Park et al, 2003). Other groups have noted that while iNOS and COX-2 are barely detectable in resting inflammatory cells, their expression levels are transiently upregulated in response to signals such as growth factors and stress (Posadas et al, 2000;Surh et al, 2001).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…eNOS can regulate the expression of the proinflammatory molecules nuclear factor-κB (NF-κB) and COX-2 (19-21). Park et al (22) demonstrated that NO could increase COX-2 expression in many different cancer cell lines, including liver, cervical, and gastric cancer. They also reported that endogenous NO produced by NOS plays a key role in COX-2 expression and proposed that iNOS inhibitors could be used to regulate COX-2 expression in head and neck squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of COX-2 activity by celecoxib reduces these effects, thereby suppressing angiogenesis and decreasing tumor growth (30). Park et al (22) reported that cross-talk exists between COX and NOS in head and neck cancer cell lines. There are inter- actions between COX and NOS pathways among host tissues, not only in tumor tissue (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%